Development of Rhyzopertha dominica (Coleoptera: Bostrychidae) on sorghum: Quality characteristics and varietal susceptibility. (May 2020) - Arthur, F.H.; Bean, S.R.; Smolensky, D.; Cox, S.; Lin, H.H.; Peiris, K.H.S.; Peterson, J.
Abstract: A white low polyphenol sorghum, a red-waxy starch sorghum, a red-tannin sorghum with moderate polyphenol levels, and a red non-tannin sorghum were evaluated for susceptibility to Rhyzopertha dominica (Fab.) (Coleopter: Bostrychidae), the lesser grain borer. Density levels of 0 (untreated controls), 10, 20, or 30 mixed-sex adults were exposed on 100 g replicates of each of the varieties and removed after two weeks. Progeny production and physical damage were evaluated on each variety, along with quality characteristics such as moisture content, protein, starch, phenolic content, and kernel vitreousity. Progeny production and physical damage varied with density level and variety, but was generally lowest on the red-waxy sorghum. At the density level of 30 parental adults more progeny were found in the red-tannin sorghum compared to the other varieties. Starch content, kernel vitreousity and hardness was lower in the red-tannin sorghum. Total phenolic content was 2–3x greater in the red-tannin sorghum compared to the other varieties, but the high phenolic content did not seem to affect R. dominica progeny production. Results suggest the insects bypassed the bran layer of the sorghum varieties to feed on the germ and endosperm. Results of this study could be used to further explore the relationships between kernel hardness, chemical composition, and susceptibility to stored product insects, and incorporate results into management programs for maintaining quality of stored sorghum and processed sorghum food by-products. Highlights: Sorghum varieties vary in susceptibility to Rhyzopertha dominica. Varietal susceptibility is linked to physical and chemical characteristics of individual varieties. Feeding damage was concentrated in the germ and endosperm region of the kernel. Feeding damage did not affect phenolic compounds in the sorghum.